Analysis of heavy metals in soft tissues of Thais Aculeata, a gastropod taken from Chendering Beach, Terengganu as an attempt to search for indicator of heavy metal pollution in the aquatic environment - Mat Amin, Nakisah; Mamat, Jamilah; Mohd. Shazili, Noor Azhar (2006)
In this study, Thais aculeata, a gastropod that commonly found on rocky beach was used to analyse the accumulation of heavy metals, viz Cu, Zn, Fe, Pb and Cd in its tissues as indication of these metal pollution in seawater around that area. The gastropods were collected from rocky shores, at Chendering, Terengganu and their soft tissues were digested as described by Agemian et al. (1980) for heavy metal contents analysis by a Atomic Absorption Spectrometry (AAS). Seawater samples were also collected from the same area and its heavy metal contents were analysed by APDC-MIBK solvent extraction method of Sturgeon et al. (1979). The results obtained in this study indicated that the concentrations of Cu, Zn, Fe, Cd and Pb in dry weight soft tissues of T. aculeata were 150.3 ± 58.0 μg.g-1 dw, 158.4 ± 27.9 μg.g- 1 dw, 316.7 ± 125.3 μg.g- 1 dw, 11.3 ± 5.9 μg.g- 1 dw and 0.6 ± 0.3 μg.g- 1 dw respectively. The concentrations of these heavy metals in seawater measured in this study were Cu (0.10 ± 0.01 μg.L-1), Zn (0.25 ± 0.06 μg. L-1), Fe (2.79 ± 1.60 μg L-1), Cd (0.48 ± 0.03 μg L-1) and Pb (2.11 ± 2.01 μg L-1) which were relatively low compared with their concentrations in the animal tissues except for Pb, to indicate the animal’s capability to accumulate at much higher concentration of heavy metals from the environment in its tissues. The suitability of this gastropod as indicator for heavy metal contamination in seawater especially at Chendering Beach area is discussed.